The punishment monopoly : tales of my ancestors, dispossession, and the building of the United States - Buck, Pem Davidson (Monthly Review Press, 2019)
"Why, asks Pem Davidson Buck, is punishment so central to the functioning of the United States, a country proclaiming 'liberty and justice for all'? Using stories of her European ancestors, who arrived in colonial Virginia in the seventeenth and eighteenth centuries, and following their descendants into the early nineteenth century, Buck shows how struggles over the right to punish, backed by the growing power of the state governed by a white elite, made possible the dispossession of Africans, Native Americans, and poor whites"--